Mechanical properties characterization of adhesively bonded T-joint at elevated temperature - Izzawati Basirom (School of Mechatronic Engineering, 2016)
In this study, the effects of elevated temperature on the adhesive strength of T-joint concerning the variation on geometry in terms of bondline thickness are investigated in parametric studies. These parameters vary between 0.5 mm to 2.0 mm, room temperature to 100 °C for adhesive thickness and testing temperature, respectively. The materials of stainless steel 304L and Araldite Standard epoxy adhesive are assessed at various thickness at elevated temperature. The material selected for adherent selected is based on the study cases application of real structural joining in fluidization bed. Several test specimens made from actual perforated plate are used to simulate the real structure of fluidization bed equipment. The experiment is conducted on a T-joint specimen and bulk specimen subjected to uniaxial tension loading using Universal Tensile Machine (UTM). Uniaxial of static tests, performed on adhesive bulk specimens in order to define accurately the constitutive behaviour in the FE models.